Study on elastic constants of polymer modified steel fibre reinforced high strength concrete with high fibre volume fraction - Deshpande, Praphulla K.; Sangle, Keshav K.; Ghugal, Yuwaraj M. (Journal of Structural Engineering, 2024)
The paper deals with the experimental and theoretical results of elastic constants of polymer modified high strengthconcrete with high fibre volume fraction. To evaluate elastic properties of this composite system, compressive strength,flexural strength, shear strength and corresponding load deformation responses were examined experimentally. Elasticproperties such as modulus of elasticity, shear modulus and Poisson’s ratio are first obtained based on experimentalresults. Simplified equations based on micromechanics, and solid mechanics theories are utilized for the evaluationof elastic properties of polymer modified randomly oriented short steel fibre reinforced high strength concrete. Themicromechanics equations for the modulus of elasticity, the shear modulus and the Poisson’s ratio are based on thefibre volume fraction and the elastic moduli of the fibre and polymer modified concrete matrix. The existing empiricalequations are also used to obtain elastic constants. These equations are applied in the full range of fiber volume fraction(1% to 10%). The comparison of experimental results with theoretical values shows the good agreement with each other.The novelty of the present paper is that the modulus of elasticity of this composite system is obtained experimentallyusing four point bending test and the Poisson’s ratio is obtained as a function of flexural and compressive strengthswith sufficient accuracy.